Review of Kostis Kornetis’ Children of the Dictatorship: Student Resistance, Cultural Politics and the "Long 1960s’" in Greece - Voglis, Polymeris (Historein, 2015)
Book review of Kostis Kornetis, Children of the Dictatorship: Student Resistance, Cultural Politics and the ’Long 1960s’ in Greece, New York and Oxford: Berghahn Books, 2013. 373 pp.